2014
DOI: 10.9734/bjmmr/2014/11005
|View full text |Cite
|
Sign up to set email alerts
|

Sex Determination Potential from Canine Tooth Dimensions

Abstract: Aims:• This study was conducted to know sex determination potential from mesiodistal dimensions of permanent canines. • To find out the average size of canines in males and females of south Indian population. • To compare the findings with National and International Studies. Study Design: The subjects were selected based on the inclusion and exclusion criteria set forth for the study. Measurements of mesiodistal widths of the four canines were made on the dental casts of each of the 600 subjects with Digital c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 16 publications
(28 reference statements)
0
6
0
Order By: Relevance
“…The present study also noted significant differences of all the measurements (mesio-distal, Labio-lingual, crown height) of the sexes, which supports the literature on sexual dimorphism. [1,2,4,8,9,10,12,13,14,15,16,23,24,25] although some studies reported no significant sex difference in tooth dimensions. [26,27] Dimorphism was greater for mandibular teeth than for maxillary teeth as greatest percentage of sexual dimorphism demonstrated for mesiodistal width in right mandibular canine followed by mesiodistal width of left mandibular canine in the present study.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…The present study also noted significant differences of all the measurements (mesio-distal, Labio-lingual, crown height) of the sexes, which supports the literature on sexual dimorphism. [1,2,4,8,9,10,12,13,14,15,16,23,24,25] although some studies reported no significant sex difference in tooth dimensions. [26,27] Dimorphism was greater for mandibular teeth than for maxillary teeth as greatest percentage of sexual dimorphism demonstrated for mesiodistal width in right mandibular canine followed by mesiodistal width of left mandibular canine in the present study.…”
Section: Discussionmentioning
confidence: 99%
“…Identification of highly damaged dead bodies such as burnt human remains, in explosions, in aviation accidents, immersed human remains in train crash, suicidal attacks, wars, massacre and hidden decomposed bodies in mass graves, cannot be verified using typical methods, as these bodies are beyond recognition in most of the time after these incidents. [1,2] Therefore, identification of these dead bodies is paramount important especially in medico-legal death investigations such as criminals and other relevant lawsuits that do not have any direct evidence for an unbiased judgment [1] .…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations